CORRELATION METHODS FOR IMAGE RECOGNITION BY VOTING SYSTEMS FRAGMENTS - Gorokhovatskiy, V. A.; Peredriy, Ye. O. (Radio Electronics, Computer Science, Control, 2008)
The results of the application of voting procedures in correlation methods of image recognition are shown. The ways of construction systems of fragments are studied. The recognition problem is formalized. The variety of voting procedures, the ways of choosing fragment characteristics and the establishment of the conformity between them are analyzed. The efficiency of the suggested approach is confirmed by the experimental results.